EXPLORING GLOBAL RESEARCH TRENDS IN SUSTAINABILITY ACCOUNTING AND ESG REPORTING - Riyanto Tri Wijaya, Juli; Aditya Dwi Prihamono; Syarif Hidayatullah; Rizky Kurniawan (Universitas Kristen Krida Wacana, 2025)
This study explores global research trends in sustainability accounting and ESG reporting through a bibliometric analysis of Scopus-indexed publications from 2015 to 2025. A total of 191 journal articles were analyzed based on publication output, sources, authorship, funding sponsors, countries, and subject areas. The results show a rapid increase in research after 2020, underscoring the importance of sustainability accounting and ESG reporting in addressing climate change, governance, and social responsibility. Research dissemination has also expanded, moving from specialized sustainability journals to broader business and accounting outlets. While Europe and the United States dominate contributions, emerging economies such as India, Malaysia, and Indonesia are gaining presence. The study concludes that sustainability accounting and ESG reporting have become mainstream academic and regulatory priorities, driven by policy, institutional, and scholarly interest. Implications arise for policymakers in harmonizing reporting standards, corporations in enhancing legitimacy and stakeholder trust, and academics in identifying emerging themes. Future research should address gaps in assurance practices, regional disparities, and the role of digital innovations such as AI and blockchain in advancing ESG reporting.